1985
DOI: 10.1073/pnas.82.18.6245
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hybrid class I genes of the major histocompatibility complex in mouse L cells.

Abstract: The class I genes of the major histocompati-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 24 publications
(48 reference statements)
1
23
0
Order By: Relevance
“…Chimeric MHC class I genes have been useful in identifying coding sequences for the antigenic determinants recognized by humoral and cellular immune responses (7,(17)(18)(19)(20), analyzing the function of the transmembrane domain (21,22), and defining sequences that control tissue-specific expression (23,24). In past studies, we noted that L cells transfected with TL coding genes expressed low levels of TL antigen, in contrast to high H-2 expression after transfection of H-2 coding genes.…”
Section: Discussionmentioning
confidence: 99%
“…Chimeric MHC class I genes have been useful in identifying coding sequences for the antigenic determinants recognized by humoral and cellular immune responses (7,(17)(18)(19)(20), analyzing the function of the transmembrane domain (21,22), and defining sequences that control tissue-specific expression (23,24). In past studies, we noted that L cells transfected with TL coding genes expressed low levels of TL antigen, in contrast to high H-2 expression after transfection of H-2 coding genes.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of cell surface expression of the polypeptides encoded by the Q genes after transfection of the genes into L cells can be explained by the early translational termina tion codon at the end of the transmembrane exon. Other approaches to the study of Qa-2 region gene expression have involved the transfection of hybrid genes [44][45][46]. The constructs contained exon 1 to 3 of Q genes ligated to the 3' portion (exon 4 to the 3' untranslated region) of an H-2 class I gene.…”
Section: Expression Of the Q Region Genesmentioning
confidence: 99%
“…These changes result in the loss of GPI-processing, phosphatidylinositolphospholipase C-insensitive surface display and drastically reduced surface expression of the "even" Qa-2 proteins relative to the "odd" Qa-2 (20,21). It has been previously shown that higher expression levels of Q8 can be restored by swapping their 3Ј gene regions with the corresponding exons of the classical class I MHC genes (22). In this model, to enhance the surface display and allow for serological monitoring of the even Qa-2 products in transfected tumors, we substituted exons 4 and 5 of Q8 with exons 4 and 5 of Q9.…”
Section: Tap-dependent Expression Of Q8 On the Surface Of Transfectedmentioning
confidence: 99%
“…To determine whether B78H1 TAP-positive transfectants support expression of Q8 with previously defined serological properties (22,23), transfectants were stained with additional mAbs. Fig.…”
Section: Tap-dependent Expression Of Q8 On the Surface Of Transfectedmentioning
confidence: 99%